2014
DOI: 10.1016/j.amepre.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The 18-Month Impact of Special Supplemental Nutrition Program for Women, Infants, and Children Food Package Revisions on Diets of Recipient Families

Abstract: Background Beginning in 2009, the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) revised its food packages and provided more whole grains, fruits, and vegetables, and fewer foods with high saturated fat content. However, knowledge of the impact of this policy shift on the diets of WIC participants remains limited. Purpose To examine the longer-term impact of the 2009 WIC food package change on nutrient and food group intake and overall diet quality among African American and Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…23 The WIC package change also included a shift toward offering lower fat milk, and previous studies demonstrated a favorable effect on children's saturated fat intake that may be attributable to this change. 10,[12][13][14]23 Dairy intake was high at baseline, and did not go down with the mandated shift in the kind of milk offered. Of note, Fatty Acids scores increased more for WIC participants than for nonparticipants, presumably due to substitutions away from high-fat milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The WIC package change also included a shift toward offering lower fat milk, and previous studies demonstrated a favorable effect on children's saturated fat intake that may be attributable to this change. 10,[12][13][14]23 Dairy intake was high at baseline, and did not go down with the mandated shift in the kind of milk offered. Of note, Fatty Acids scores increased more for WIC participants than for nonparticipants, presumably due to substitutions away from high-fat milk.…”
Section: Discussionmentioning
confidence: 99%
“…Using rigorous methods of dietary assessment and a nationally representative sample from NHANES, our study results are consistent with earlier findings from regional studies. 4,10,[12][13][14] It has been shown that WIC participation is associated with better nutrient intake among preschool-aged children compared with their peers who are also from low-income households. [20][21][22] In this analysis, children in WIC households between 2003 and 2008 had a diet quality score that was higher than that of their peers by >2 points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The New York State (NYS) WIC Program has been actively and progressively promoting these and other healthy living activities since 1997 [8,9], and the NYS WIC program was the first in the nation to implement the required USDA food package changes in January 2009. Shortly after implementation of the revised WIC food package, modest changes in food consumption and purchasing patterns among WIC participants in NYS [10], and elsewhere around the country [11][12][13][14][15][16] were observed in cross-sectional studies. The current longitudinal study examines breastfeeding and other food consumption patterns in relation to the prevalence of obesity at 3 years of age in a cohort of children enrolled in the NYS WIC Program as infants in 2008-2009.…”
Section: Introductionmentioning
confidence: 99%
“…Families participating in federal nutrition programs nationwide were more likely to have unhealthy grocery store purchases than were families who did not participate; the article estimates that the Supplemental Nutrition Assistance Program (SNAP) paid at least $1.7 billion to $2.1 billion annually for SSBs purchased in grocery stores (3). Public health policy has been looking into how to change these programs to give more emphasis to healthier options (4,79), and this remains a promising area for intervention.…”
Section: Limit Marketing Of Ssbs and Minimize Marketing's Impact On Cmentioning
confidence: 99%